Coacervation of biopolymers on muscovite surface - Chen, Jiaxin; Liu, Zhijun; Li, Yanzhang; Bai, Qingwen; Li, Yan; Liang, Dehai (Frontiers in Soft Matter, 2022)
The first life was believed to emerge in the early Earth via a process involving synthesis of organic compounds and formation of protocells. However, it is still a puzzle how the protocell with hierarchal structure and desirable functions was spontaneously generated in the non-living environment composed of mainly water and minerals. In this work, using muscovite as an example of minerals, we systemically studied the coacervation of poly(L-lysine) (PLL), quaternized dextran (Q-dextran), and single-stranded oligonucleotide (ss-oligo) on muscovite surface at varying mixing orders. Only when Q-dextran firstly interacts with muscovite surface to form a coating layer, followed by the addition of ss-oligo and PLL, the formed coacervates exhibit distinct and versatile morphologies, including spherical PLL/ss-oligo droplets on the surface, floating PLL/ss-oligo droplets above the Q-dextran/ss-oligo blanket, and PLL/ss-oligo islands surrounded by the Q-dextran/ss-oligo sea. The kinetic pathway to the resulting morphology is specific in each case. There results suggest that polysaccharide was probably the first biopolymer accumulated on the mineral surface in early Earth. The sugar coating provides a “nest” for protein/peptide and DNA/RNA to from sub-compartment and to further develop advanced functions.